The Lost Tribes of Israel – and the Genesis of Christianity in Fiji: Missionary Notions of Fijian Origin from 1835 to Cession and Beyond. Issue 3 (14th October 2015) - Newland, Lynda
Abstract: The idea that certain iTaukei (formerly 'Fijian') clans are descended from the Jews, particularly through a Lost Tribe of Israel, is very strong among some contemporary clans and church groups in Fiji. The importance of the Lost Tribes was reinforced in the 1987 coups, when it formed part of the political rhetoric of the coup leader, Sitiveni Rabuka, who was also a lay preacher of the Methodist Church. In order to understand such claims, I review the historical record from 1835 to Cession in 1874 to evaluate when the idea of the Lost Tribes began to be used and, more broadly, the extent to which Christianity was the language for engagement and/or resistance between missionaries and Fijians. At the same time, I explore the developing missionary discourses and their relationship with newly emerging ideas about the science of origins. The evidence indicates that, as certain ideas became routinised around the time of Cession, Christianity and science together provided a grammar that enabled many Fijians to strongly identify with the Old Testament.